The Pinnacle Sunway, Subang / Muhammad Hafizuddin ... [et al.] - Muhammad Hafizuddin, Azmi; Muhammad Asyraf, Mohd Nasir; Nabihah, Jamaludin; Nur Arifa, Mohd Yussof; Afiqah Batrisyia, Abdul Aziz (2019)
The main purpose for this assignment is to let students gain some knowledge about maintenance organization in a building and how to prepared maintenance organization. In this report, there will be 9 chapters which include the detail of the property, the background of maintenance organization, maintenance policy, maintenance programmed and planning, building design and concept, building condition assessment, maintenance strategy, and legal aspect. In this report, there also included about the tenancy in the building but not in specific details because some of the documents are confidential. Moreover, this report includes about the financial aspect of the building in terms of income and expenditure of the building. These chapters include maintenance forecast for 3 years ahead. The students are using the method of interview and site visit to obtain all the information that needed in this report. Lastly, this report also contains problems and recommendation in chapter 9 which explain every problem that students identified about the building.